Past and future hymenaioi: Euripides’ Iphigenia in Tauris and The Trojan Women - Napoli , Juan Tobías (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2021)
Among the numerous references that we find in Euripides' tragedies to the hymenaios, we will try to understand their literary meaning in two of his works: the hymenaios remembered by the women who form the choir of Iphigenia in Tauris and those of The Trojan Women: the past and future hymenaios Hecuba talks about, as well as the imminent hymenaios that Casandra executes in advance, putting into work her mother's foresight. Many of the values of these celebrations have to do with the traditional rite of marriage and have often been analyzed from this historical perspective. However, we will try to show that the poet uses them with a new, literary value, mainly ironic or contrasting.